2017
DOI: 10.1155/2017/1754696
|View full text |Cite
|
Sign up to set email alerts
|

Association between Recipient IL-15 Genetic Variant and the Prognosis of HBV-Related Hepatocellular Carcinoma after Liver Transplantation

Abstract: Objective To investigate the association of donor and recipient IL-15 genetic variants with HCC recurrence and prognosis after LT. Methods A total of 112 liver transplant patients with HBV-related HCC were enrolled. IL-15 rs10519613 and rs13122930 were genotyped in donors and recipients. Results Recipient IL-15 rs10519613 polymorphism was found to be significantly related to HCC recurrence after LT. In multivariate analysis, tumor thrombus, UCSF criteria, and recipient IL-15 rs10519613 genotypes were independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In previous studies, Rap1A gene over-expression had been reported in various cancers, including ovarian cancer [10], breast cancer [18], and OCSCC [13]. The relationship between SNP genotype and HCC recurrence after LT has been reported in VEGF gene [19], IL-15 gene [20] and HPSE gene [21], signifying that the SNP genotype of hosts, including recipients and donors, has a significant role in the progression of HCC recurrence after LT.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, Rap1A gene over-expression had been reported in various cancers, including ovarian cancer [10], breast cancer [18], and OCSCC [13]. The relationship between SNP genotype and HCC recurrence after LT has been reported in VEGF gene [19], IL-15 gene [20] and HPSE gene [21], signifying that the SNP genotype of hosts, including recipients and donors, has a significant role in the progression of HCC recurrence after LT.…”
Section: Discussionmentioning
confidence: 96%
“…Two studies showed that rs10519613 in IL15 was associated with the risk of minimal residual disease (MRD) in pediatric acute lymphoblastic leukemia (57,58). Zhang et al (59) observed that rs10519613 was associated with poor prognosis of HBV-related hepatocellular carcinoma after liver transplantation. In this study, we found that rs10519613 was associated with worse PFS and OS in advanced NSCLC patients treated with EGFR-TKI.…”
Section: Discussionmentioning
confidence: 99%
“…There is much focus on genetic determinants and the development of HCC after DAAs therapy in recent years such as human leukocyte antigen, IL28B, IL-15 and OAS variants [ 10 , 12 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%